Theologische Positionen zu Transhumanismus und KI - ein Überblick - Oorschot, Frederike van (de Gruyter, 2023)
The paper maps the German theological debate on AI and transhumanism. Eleven topoi of theological discourse on AI and transhumanism are elaborated: the human as creator of the machine; human-like machine; machine-like human; end of sociality; end of (responsible) agency; end of freedom; reality control of machines; end of an ontology of creation; abolition of death; singularity; transhumanism as religion or ideology. The reconstructions of the topoi reveal a strong anthropological focus, whereby the emerging technology imaginary is strongly shaped by theological anthropology – rather than by current technologies. This phenomenon of a “mirror imaginary” is discussed as it concerns its implications for further theological reflection.
In: Zeitschrift für Pädagogik und Theologie, 75 (2023), Nr. 2. pp. 139-151. ISSN 1437-7160 (Druck-Ausg.); 2366-7796 (Online-Ausg.)